Acoustic Methods to Monitor Protein Crystallization and to Detect Protein Crystals in Suspensions of Agarose and Lipidic Cubic Phase. (February 2016) - Ericson, Daniel L.; Yin, Xingyu; Scalia, Alexander; Samara, Yasmin N.; Stearns, Richard; Vlahos, Harry; Ellson, Richard; Sweet, Robert M.; Soares, Alexei S.
Improvements needed for automated crystallography include crystal detection and crystal harvesting. A technique that uses acoustic droplet ejection to harvest crystals was previously reported. Here a method is described for using the same acoustic instrument to detect protein crystals and to monitor crystal growth. Acoustic pulses were used to monitor the progress of crystallization trials and to detect the presence and location of protein crystals. Crystals were detected, and crystallization was monitored in aqueous solutions and in lipidic cubic phase. Using a commercially available acoustic instrument, crystals measuring ~150 µm or larger were readily detected. Simple laboratory techniques were used to increase the sensitivity to 50 µm by suspending the crystals away from the plastic surface of the crystallization plate. This increased the sensitivity by separating the strong signal generated by the plate bottom that can mask the signal from small protein crystals. It is possible to further boost the acoustic reflection from small crystals by reducing the wavelength of the incident sound pulse, but our current instrumentation does not allow this option. In the future, commercially available sound-emitting transducers with a characteristic frequency near 300 MHz should detect and monitor the growth of individual 3 µm crystals.